LEARNER AUTONOMY AND INFORMATION SKILLS DEVELOPMENT IN THE FACULTIES OF ARTS AND HUMANITIES - Alevtina B. Klimova; Elena V. Khohlushina (Высшее образование в России, 2016)
The article describes a course "Learner Autonomy and Information Skills Development Through the Internet In the Faculties of Arts and Humanities" which was developed by request of the Ministry for Education and Science within the project "Remodeling Higher Pedagogic Education". The main course goal is developing autonomous information and learning skills of Humanities Faculties students with the help of the Internet. Consequently, two key groups of skills that are to evolve during this course include 1) self-directed learning skills and 2) information skills. One of the basic instruments that allows developing and at the same time controlling these skills is an Action plan aimed at organizing students' work to achieve their learning goals. Essential components of the plan include a specific goal, tasks, realistic and achievable actions indicating at what exactly will be done and who will perform it, resources to be used, realistic time limits and possible challenges. Reflection practices, interaction activities in class and on the distance educational platform Sakai and project work serve as necessary means to realize goals set for the course.